Long-term follow-up results of patients with sarcomatoid RCC: A retrospective evaluation of a single center experience - Eraslan, Emrah; Yalçıntaş, Ülkü (Journal of Surgery and Medicine, 2020)
Aim: Sarcomatoid renal cell cancer (sRCC) is an extremely rare condition, and literature on disease management is limited. There are no treatment recommendations based on high-quality data. Our aim in this study is to reveal our long-term experience with patients diagnosed with sRCC. Methods: Patients who were followed up with a diagnosis of sRCC between January 2010 and December 2019 were retrospectively evaluated in terms of main disease characteristics, treatments, treatment responses and survival times. Results: Twenty-five (8.0%) of 311 RCC patients had sarcomatoid differentiation. The median age of the 25 patients included in the study was 58.1 (26.3-78.0) years, and the vast majority were male (n=18, 72%). Distant organ metastasis was present in 11 (44.0%) patients at the time of diagnosis. In 10 (71.4%) out of 14 patients who underwent curative surgery, recurrence was observed with distant organ metastasis. Thirteen (61.9%) of 21 metastatic patients received tyrosine kinase inhibitor (pazopanib or sunitinib) in second-line treatment. The progression-free survival for the second line treatment of these 13 patients was 6.1 months (95% CI: 3.8-8.4). Long-term disease control was achieved in one of the two patients who received nivolumab treatment. Cytoreductive nephrectomy was performed in seven (63.6%) of the 11 patients who were in metastatic stage at the time of diagnosis. Pulmonary metastasectomy was performed in two patients with lung metastasis. One of these two patients was still followed up without recurrence at the 112th month after metastasectomy. Overall survival was 10.8 months (85% CI: 8.9-12.6) for 21 patients in the metastatic stage. Conclusion: sRCC is a rare disease with a poor prognosis. Systemic treatment efficacy is low with frequent distant metastases. Tyrosine kinase inhibitors are prominent among current treatment methods. Immune checkpoint inhibitors, one of the new generation treatment options, is promising in terms of treatment success. The addition of cytoreductive nephrectomy and metastasectomy to the treatment process may provide additional benefits.